Greek Students as Users of the Spanish Language - Kapeta, Chrysovalantou (Randwick International of Education and Linguistics Science Journal, 2025)
A database in foreign language education can facilitate the educational community in distinguishing language levels and the degree of readability through the investigation of specific factors. For this purpose, 60 samples of written language production of Greek students of the Aristotle University of Thessaloniki, who study in different departments, were collected. These are texts from the last decade and concern the A1 language level. After the samples were collected by random drawing, they were digitized manually in word format. The results were manually exported to an Excel file, which was used to perform statistical analysis in the Tableau tool. The main purpose of this study is to highlight particular characteristics, difficulties or advantages of Greek students who use Spanish as an elective subject. Morphological, grammatical, syntactic or lexical variables shape the beginner profile of non-native speakers of the Spanish Language for level A1, while factors such as the number of features, words, sentences, the gender of the users and the degree of difficulty of the produced texts could create a significant database, useful for future research at a national and international level. The final product of this study results in the most accurate and perhaps most reliable distinction of language levels for a potentially more effective use of languages by non-native speakers if there is subsequent research at all levels of language proficiency and in more languages.